Leadership Style of Madrasah Principal in Improving Teacher Professionalism at Madrasah Aliyah - Ema Apriana; Andi Warisno; Nur Hidayah (Journal Corner of Education, Linguistics, and Literature, 2023)
Education for the Indonesian people today is an absolute necessity that must be developed. Education that is managed in an orderly, orderly, and efficient manner can achieve lofty goals, namely creating justice, prosperity, and intelligence for the Indonesian people. The head of the madrasa as an educational leader, judging from the status and method of appointment, is classified as an official leader, "formal leader", or "status leader". His position as a "leader status" can also increase to become a "functional leader", or "operational leader", depending on his achievements and abilities in playing the role of an educational leader at the madrasa who has been given responsibility for it. This study formulates the problem: how the madrasa principal's leadership style improves teacher professionalism and what factors are the supporters and obstacles to the madrasa principal's leadership style in improving teacher professionalism at MA Ma'arif NU 5 Sekampung. This research is descriptive qualitative. Data was collected through interviews, observation, and documentation. After the data is collected and analyzed by means of data reduction, data presentation and drawing conclusions. Based on the results of the study, it can be concluded that the leadership style of the madrasah principal in improving teacher professionalism at MA Ma'arif NU 5 Sekampung went well because of the quality of human resources. The supporting factors for the leadership style of the madrasa principal in improving teacher professionalism are human resources, the madrasa environment and a harmonious work climate, facilities and infrastructure, and community and institutional participation. While the inhibiting factors are students who are not interested in the learning process, the educational background of teachers who have not mastered the curriculum and teacher education that has not been linear.